Antipruritic effect of natural superoxide dismutase : sensory evaluation - Diehl, Christian (Array, 2009)
Summary: The primary objective of the study was to evaluate the antipruritic effect of natural superoxide dismutase in the cosmetic product Sodermix® cream. In this randomized intra-individual study including 15 volunteers, 14 female and one male, mean age 41±4 (range 18-66) years, the cosmetic product Sodermix® cream was evaluated according to the Dermscan Group protocol by recording thermal sensitivity levels using Cutaneous Thermal Sensitivity analyzer before and 30 and 90 minutes after the product application. The study was conducted from April to June 2008. Study results showed a decrease in the lengths of pruritus 30 minutes of the product application onto the treated zone and a significant decrease in pruritus intensity 90 minutes of the product application onto the treated zone. The study allows for evaluation of physical sensation and quantification of heat with cutaneous thermal sensitivity measurements as a psycho-physical method to evaluate variables of thermal sensations in relation to variables by thermal stimuli. The study demonstrated a significant antipruritic effect of Sodermix cream